Glyceryl ether (mono-tert-butoxypropanediol) in emulsion system - Yusrabbil Amiyati Yusof,; Azhar Ariffin,; Zafarizal Aldrin Azizul Hasan, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This paper reports the effects of glyceryl ether specifically mono-tert-butoxypropanediol on oil in water emulsion system. Based on 12 HLB value, screening for stable emulsions was carried out without the presence of glyceryl ether. A stable emulsion was used as a control. Then the effects of glyceryl ether on the emulsion system were investigated. The emulsions prepared were analyzed for stability, viscosity, pH value, particle size, in vitro dermal irritation potential, in vitro ocular irritation potential and also moisturizing property. The incorporation of glycerol in the emulsion system was also done for comparison. Emulsions with glyceryl ether showed lower viscosity values than emulsions with glycerol. Furthermore, the emulsions also exhibited moisturizing property compared to the control emulsion. Glyceryl ether is suitable to be used in cosmetic products which require reduced viscosity but retain its skin hydration property.